Ecumenical Catholic Learning: Synodality in the Anglican–Roman Catholic Church Dialogue - Okpaleke, Ikenna Paschal (Asian Horizons, 2020)
There is an increasing awareness of the necessity of synodality in the ecclesiology of the Roman Catholic Church. While this awareness may be attributed to the programme and governance style of Pope Francis, there is also the question of whether synodality could be defined as a subject of ecumenical learning particularly within the context of the international Anglican-Roman Catholic dialogue (ARCIC). To understudy this element of ecumenical learning vis-à-vis synodality, this article examines the idea of ecumenical learning within the context of ARCIC dialogue, analyzes the subject matter of synodality in ARCIC documents in comparison to the increasing awareness of synodality within the Roman Catholic Church, and finally argues for a sustained practice of synodality as a deepening of a pneumatological ecclesiology within the Church. Indeed, where an ecumenical learning is established, it creates the possibility of other forms and subjects of mutual learning thereby reaffirming the conviction that ecumenical dialogue is never a fruitless venture.